A memristor with adjustable memristive behavior and a control method thereof
By using phase change materials in the memristor to prepare the dielectric layer and adjust its phase change through heating and humidity treatment, the problem of conductive filaments in the prior art relying on single electrical excitation and multiple field inputs, and the memory resistance is achieved Flexible control of behavior and high programming flexibility.
Patent Information
- Application Number
- CN202311523071.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-14
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2043-11-14
AI Technical Summary
The conductive filament formation of existing redox memristors mainly relies on electrical excitation operations, and multiple field inputs (such as light fields and electric fields) affect the construction of low-power devices, making it difficult to achieve high programming flexibility.
The dielectric layer is prepared by using phase change materials, and the dielectric layer is phase-changed through heating and humidity treatment, thereby regulating the memristor behavior and realizing the transformation from memristorless behavior to gradual memristor behavior.
It significantly improves the programming flexibility of memristors, and controls the memristor behavior through phase change of the dielectric layer, which is suitable for the construction of low-power devices.
Smart Images

Figure CN117677281B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of information science, and in particular to a memristor with adjustable memristive behavior and a control method thereof. Background Art
[0002] Memristor is a non-volatile memory device that has received widespread attention worldwide in recent years. It has great application prospects in fields such as information storage and neuromorphic analog chips. Memristor has the advantages of simple structure, small size, rewritable, low operating voltage, and non-volatility. The basic structure is a "metal-dielectric layer-metal" structure. The material selection of the dielectric layer is also extremely wide. Semiconductor or insulator materials can be used to prepare the dielectric layer. Common materials include metal oxides, organic matter, two-dimensional materials, etc. The choice of metal usually uses silver as the active electrode to construct a redox memristor. Under the action of the electric field, conductive filaments will be formed that penetrate the dielectric layer, and the reverse electric field excitation will cause the conductive filaments to partially break, and the conductivity state of the device will also change accordingly, so that data storage can be achieved. In the context of big data, the Internet of Things, and artificial intelligence, people are paying more and more attention to the performance regulation of memory. The development of memristors with adjustable memristive behavior is conducive to enhancing the commercial application potential of memristors.
[0003] For redox memristors, the formation of conductive filaments involves three steps (taking silver as an example for the active anode material): 1) oxidation of the metal at the anode (Ag→Ag + +e); 2) Migration of metal ions; 3) Reduction of metal ions at the cathode (Ag + +e→Ag). The formation and training of the conductive filaments of redox memristors mainly rely on electrical excitation operations, and most devices are single physical mechanisms. Some studies have constructed memristors with adjustable memristive behavior through environmentally sensitive (light, humidity, chemical gases, etc.) dielectric layers, but such materials usually require the input of multiple external fields. For example, in the light-controlled memristive behavior, it is necessary to apply both the light field and the electric field. The multi-field-controlled memristive behavior affects the construction of low-power devices.
[0004] Therefore, the prior art still needs to be improved and developed. Summary of the invention
[0005] In view of the above-mentioned deficiencies in the prior art, the purpose of the present invention is to provide a memristor with adjustable memristive behavior and a control method thereof, aiming to construct a memristor with adjustable memristive behavior by preparing a dielectric layer using phase change material, thereby improving the programming flexibility of the memristor.
[0006] The technical solution of the present invention is as follows:
[0007] A first aspect of the present invention provides a memristor with adjustable memristive behavior, comprising: a substrate, an active electrode, an inert electrode, and a dielectric layer disposed between the active electrode and the inert electrode, wherein the material of the dielectric layer is a phase change material.
[0008] Specifically, the present invention uses phase change material as the dielectric layer, which will significantly affect the formation, migration and reduction process of active electrode cations before and after the phase change, and can achieve differentiated conductive filament dynamic behavior, thereby realizing the regulation of the memristor's memristive behavior.
[0009] Optionally, the dielectric layer is transformed from the first phase to the second phase by heat treatment, and is transformed from the second phase to the first phase by humidity treatment. Preferably, the temperature of the heat treatment is 160° C.-200° C.; preferably, the humidity of the humidity treatment is 80-100%.
[0010] Specifically, the dielectric layer is transformed from the first phase to the second phase by heating at 160°C-200°C. On the one hand, this temperature range is significantly higher than the ambient temperature and is not easily affected by the ambient temperature, which can improve the stability of the memristor; on the other hand, this temperature range can be achieved by conventional heating means, which can improve the applicability of the memristor of the present invention.
[0011] The dielectric layer is transformed from the second phase to the first phase after being treated with 80-100% humidity. On the one hand, this humidity range is significantly higher than the ambient humidity and is not easily disturbed by the ambient humidity, which can improve the stability of the memristor; on the other hand, this humidity range can be achieved by conventional humidification means, which can improve the applicability of the memristor of the present invention.
[0012] Optionally, the phase change material is a perovskite selected from one of CsPbIBr2, CsPbI3, CsPbI2Br, and CsPbBr3.
[0013] Specifically, CsPbIBr2, CsPbI3, CsPbI2Br, CsPbBr3, etc. have good photoelectric properties and stability, which can improve the efficiency and long-term stability of memristors.
[0014] Optionally, the deposition thickness of the dielectric layer is 50-80 nanometers.
[0015] Specifically, when the thickness of the dielectric layer is too thin, it will affect the stability and tolerance of the memristor; when the thickness of the dielectric layer is too thick, it will affect the operating voltage and power consumption. In the present invention, when the deposition thickness of the dielectric layer is 50-80 nanometers, the memristor has better performance as a whole.
[0016] Optionally, the material of the substrate is one or more of silicon oxide, glass, quartz, polyethylene naphthalate, and polyethylene terephthalate.
[0017] Specifically, in the present invention, the function of the substrate is to provide support and foundation, and a suitable substrate material can be selected according to specific application requirements, manufacturing process and budget.
[0018] Optionally, the material of the active electrode is one of silver, copper, nickel, lithium and sodium.
[0019] Specifically, in the present invention, the active electrode plays a role in storing and releasing electric charge. When a positive voltage is applied to the active electrode, the active metal electrode releases metal ions, which move in the dielectric layer of the memristor. Suitable active electrode materials can be selected according to specific application requirements, manufacturing processes and budgets.
[0020] Optionally, the material of the inert electrode is one of indium tin oxide, aluminum, platinum, gold, titanium, graphene, and fluorine-doped tin oxide.
[0021] Specifically, in the present invention, the inert electrode plays the role of receiving and reducing metal ions. When metal ions move from the active electrode to the dielectric layer of the memristor, they are reduced to metal atoms on the inert electrode. The appropriate electrode material can be selected according to the specific application requirements, manufacturing process and budget.
[0022] A second aspect of the present invention provides a method for regulating a memristor as described above, comprising: humidifying the memristor to place the dielectric layer in a first phase; and heating the memristor to place the dielectric layer in a second phase.
[0023] Specifically, the present invention realizes the regulation of memristive behavior based on the phase change of the dielectric layer. The dielectric layer is placed in the first phase by humidification treatment, and the memristor has no memristive behavior at this time. The dielectric layer is changed from the first phase to the second phase by heating treatment, and the memristor has a gradual memristive behavior at this time. If the dielectric layer is subjected to humidity treatment again, the first phase can be restored, and the memristive behavior disappears.
[0024] Beneficial effects: Compared with the prior art, the present invention adopts phase change material to prepare the dielectric layer, constructs a memristor with completely different memristive behavior before and after the phase change, realizes the transition from non-memristive behavior to gradual memristive behavior, and significantly improves the programming flexibility of the memristor. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 Schematic diagram of the structure of a memristor.
[0026] Figure 2 This is the phase transition diagram of the perovskite film in Example 1.
[0027] Figure 3The diagram shows the electrical performance of the memristor before and after phase change. DETAILED DESCRIPTION
[0028] The present invention provides a memristor with adjustable memristive behavior and a control method thereof. In order to make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail in combination with specific embodiments and drawings. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention. In addition, the characteristics, operations or features described in the specification can be combined in any appropriate manner to form various implementation methods. At the same time, the steps or actions in the method description can also be replaced or adjusted in order in a manner that is obvious to those skilled in the art. Therefore, the various sequences in the specification and drawings are only for the purpose of clearly describing a certain embodiment, and do not mean that they are necessary sequences, unless otherwise specified that a certain sequence must be followed. The serial numbers themselves, such as "first", "second", etc., for the components in this article are only used to distinguish the objects described and do not have any order or technical meaning. The instruments and reagents used are all commercially available products.
[0029] like Figure 1 As shown, the memristor of the present invention comprises: a substrate 10, an inert electrode 20 disposed on the substrate 10, a dielectric layer 30 disposed on the inert electrode 20, and an active electrode 40 disposed on the dielectric layer 30. The material of the dielectric layer is a phase change material.
[0030] Example 1
[0031] In this embodiment, inorganic perovskite (CsPbIBr2) is used as the dielectric layer material to prepare a redox memristor based on the dielectric layer phase change to regulate the memristor behavior.
[0032] The two-terminal structure of metal-dielectric layer-metal will be used to prepare the memristor of this scheme.
[0033] The memristor will be prepared on a glass substrate with an ITO electrode (ITO thickness is 30 nanometers). First, a 2 cm*2 cm ITO glass substrate is placed in acetone and ultrasonically cleaned for 5 minutes. Then, the substrate is blown dry with nitrogen for later use.
[0034] The perovskite film was prepared by a dual-heat source thermal evaporation method. CsI and PbBr2 powders were placed in two different crucibles, placed in a thermal evaporator, and evacuated to 10 -6Torr. The two crucibles were heated separately, and the evaporation rates of CsI and PbBr2 were adjusted to 0.65 and 0.61 angstroms per second, respectively. The deposition thickness of the perovskite film was 50 nanometers. At room temperature, the perovskite film is in a non-perovskite phase. The perovskite film can be transformed into the perovskite phase by placing it on a heating table and heating it at 160°C for 2 minutes. The ambient humidity was increased to 80% by a humidifier, and the perovskite film was restored to the non-perovskite phase within 1 minute.
[0035] By using a mask and a thermal evaporation method at a deposition rate of 0.1 angstroms per second, a 30 nanometer thick silver electrode is prepared on the above perovskite film, thus completing the preparation of the memristor.
[0036] Example 2
[0037] In this embodiment, inorganic perovskite (CsPbIBr2) is used as the dielectric layer material to prepare a redox memristor based on the dielectric layer phase change to regulate the memristor behavior.
[0038] The two-terminal structure of metal-dielectric layer-metal will be used to prepare the memristor of this scheme.
[0039] The memristor will be prepared on a quartz substrate. First, a 2 cm*2 cm quartz substrate is placed in acetone and ultrasonically cleaned for 30 minutes. Then, the substrate is blown dry with nitrogen for later use.
[0040] An aluminum electrode with a thickness of 50 nanometers was prepared on the above substrate by using a thermal evaporation method through a mask at a deposition rate of 0.1 angstroms per second.
[0041] The perovskite film was prepared by a dual-heat source thermal evaporation method. CsI and PbBr2 powders were placed in two different crucibles, placed in a thermal evaporator, and evacuated to 10 -6 Torr. The two crucibles were heated separately, and the evaporation rates of CsI and PbBr2 were adjusted to 0.65 and 0.61 angstroms per second, respectively. The deposition thickness of the perovskite film was 60 nanometers. At room temperature, the perovskite film is in a non-perovskite phase. The perovskite film can be transformed into a perovskite phase by placing it on a heating table and heating it at 170°C for 2 minutes. The ambient humidity was increased to 85% by a humidifier, and the perovskite film was restored to a non-perovskite phase within 1 minute.
[0042] A lithium electrode with a thickness of 30 nanometers is prepared on the above perovskite film by using a thermal evaporation method through a mask at a deposition rate of 0.1 angstroms per second, thus completing the preparation of the memristor.
[0043] Example 3
[0044] In this embodiment, inorganic perovskite (CsPbIBr2) is used as the dielectric layer material to prepare a redox memristor based on the dielectric layer phase change to regulate the memristor behavior.
[0045] The two-terminal structure of metal-dielectric layer-metal will be used to prepare the memristor of this scheme.
[0046] The memristor will be prepared on a polyethylene terephthalate substrate. First, a 2 cm*2 cm polyethylene terephthalate substrate is placed in acetone and ultrasonically cleaned for 20 minutes. Then, the substrate is blown dry with nitrogen for later use.
[0047] A graphene electrode with a thickness of 40 nanometers was prepared on the above substrate by using a thermal evaporation method through a mask at a deposition rate of 0.1 angstroms per second.
[0048] The perovskite film was prepared by a dual-heat source thermal evaporation method. CsI and PbBr2 powders were placed in two different crucibles, placed in a thermal evaporator, and evacuated to 10 -6 Torr. The two crucibles were heated separately, and the evaporation rates of CsI and PbBr2 were adjusted to 0.65 and 0.61 angstroms per second, respectively. The deposition thickness of the perovskite film was 70 nanometers. At room temperature, the perovskite film is in a non-perovskite phase. The perovskite film can be transformed into a perovskite phase by placing it on a heating table and heating it at 180°C for 2 minutes. The ambient humidity was increased to 90% by a humidifier, and the perovskite film was restored to a non-perovskite phase within 1 minute.
[0049] A copper electrode with a thickness of 40 nanometers is prepared on the above perovskite film by using a thermal evaporation method through a mask at a deposition rate of 0.1 angstroms per second, thereby completing the preparation of the memristor.
[0050] Example 4
[0051] In this embodiment, inorganic perovskite (CsPbIBr2) is used as the dielectric layer material to prepare a redox memristor based on the dielectric layer phase change to regulate the memristor behavior.
[0052] The two-terminal structure of metal-dielectric layer-metal will be used to prepare the memristor of this scheme.
[0053] The memristor will be prepared on a polyethylene naphthalate substrate. First, a 2 cm*2 cm polyethylene naphthalate substrate is placed in acetone and ultrasonically cleaned for 20 minutes. Then, the substrate is blown dry with nitrogen for later use.
[0054] A gold electrode with a thickness of 50 nanometers was prepared on the above substrate by using a thermal evaporation method through a mask at a deposition rate of 0.1 angstroms per second.
[0055] The perovskite film was prepared by a dual-heat source thermal evaporation method. CsI and PbBr2 powders were placed in two different crucibles, placed in a thermal evaporator, and evacuated to 10 -6 Torr. The two crucibles were heated separately, and the evaporation rates of CsI and PbBr2 were adjusted to 0.65 and 0.61 angstroms per second, respectively. The deposition thickness of the perovskite film was 80 nanometers. At room temperature, the perovskite film is in a non-perovskite phase. The perovskite film can be transformed into a perovskite phase by placing it on a heating table and heating it at 190°C for 2 minutes. The ambient humidity was increased to 90% by a humidifier, and the perovskite film was restored to a non-perovskite phase within 1 minute.
[0056] A lithium electrode with a thickness of 50 nanometers is prepared on the above perovskite film by using a thermal evaporation method through a mask at a deposition rate of 0.1 angstroms per second, thereby completing the preparation of the memristor.
[0057] Example 5
[0058] In this embodiment, inorganic perovskite (CsPbIBr2) is used as the dielectric layer material to prepare a redox memristor based on the dielectric layer phase change to regulate the memristor behavior.
[0059] The two-terminal structure of metal-dielectric layer-metal will be used to prepare the memristor of this scheme.
[0060] The memristor will be prepared on a polyethylene naphthalate substrate. First, a 2 cm*2 cm polyethylene naphthalate substrate is placed in acetone and ultrasonically cleaned for 20 minutes. Then, the substrate is blown dry with nitrogen for later use.
[0061] A FTO electrode with a thickness of 50 nanometers was prepared on the above substrate by using a thermal evaporation method through a mask at a deposition rate of 0.1 angstroms per second.
[0062] The perovskite film was prepared by a dual-heat source thermal evaporation method. CsI and PbBr2 powders were placed in two different crucibles, placed in a thermal evaporator, and evacuated to 10 -6 Torr. The two crucibles were heated separately, and the evaporation rates of CsI and PbBr2 were adjusted to 0.65 and 0.61 angstroms per second, respectively. The deposition thickness of the perovskite film was 80 nanometers. At room temperature, the perovskite film is in a non-perovskite phase. The perovskite film can be transformed into the perovskite phase by placing it on a heating table and heating it at 200°C for 2 minutes. The ambient humidity was increased to 95% by a humidifier, and the perovskite film was restored to the non-perovskite phase within 1 minute.
[0063] A nickel electrode with a thickness of 50 nanometers is prepared on the above perovskite film by using a thermal evaporation method through a mask at a deposition rate of 0.1 angstroms per second, thereby completing the preparation of the memristor.
[0064] Example 6
[0065] In this embodiment, the memristor prepared in Embodiment 1 is tested, and the electrical performance of the memristor is evaluated using a semiconductor parameter analyzer combined with a probe station.
[0066] First, the memristor was placed in the non-perovskite phase by humidification. The voltage of the memristor was scanned back and the current change was recorded. The scanning method was: 0V→2V→0V, the step frequency was 50mV, and the scanning was continued for 10 times; then the voltage direction was changed: 0V→-2V→0V, the step frequency was 50mV, and the scanning was continued for 10 times. Secondly, the memristor was heated to 160 degrees Celsius on the heating platform and maintained for two minutes to transform the perovskite film into the perovskite phase. The electrical performance of the perovskite phase memristor was evaluated using the same test method as above.
[0067] Test results such as Figure 3 As shown, Figure 3 Figure a shows the electrical performance of the memristor in the non-perovskite phase; Figure 3 Figures b and c show the electrical performance of the memristor in the perovskite phase. Figure 3 It can be seen that in the non-perovskite phase, the memristor has no memristive behavior; in the perovskite phase, the memristor has a gradual memristive behavior.
[0068] The electrical performance of this embodiment shows that in the non-perovskite phase, the current-voltage curves of the memristor under positive and negative voltage sweeps are basically the same after ten cycles, and the current is also small, all below 10 -6 Ampere, no conductive path is formed in the dielectric layer. It can be inferred that silver ions in the CsPbIBr2 film in the non-perovskite phase are difficult to migrate and cannot form a conductive path. In contrast, in the perovskite phase, the memristor observed a gradual change in resistance in both positive and negative voltage retracements, and the resistance gradually increased in the positive direction and gradually decreased in the negative direction. It can be indirectly shown that under the action of the electric field, silver ions can migrate in a directional manner in the perovskite, gradually forming or gradually destroying the conductive path, so that the memristor has a gradual change in resistance. Therefore, the memristor prepared by the present invention can complete the regulation of the resistance behavior through the phase change of the dielectric layer.
[0069] In summary, the present invention provides a memristor with adjustable memristive behavior, comprising: a substrate, an active electrode, an inert electrode, and a dielectric layer disposed between the active electrode and the inert electrode, wherein the material of the dielectric layer is a phase change material. The present invention uses a phase change material to prepare the dielectric layer, constructs a memristor with completely different memristive behaviors before and after the phase change, realizes the transition from non-memristive behavior to gradual memristive behavior, and significantly improves the programming flexibility of the memristor.
[0070] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.
Claims
1. A method for controlling a memristor with controllable memristive behavior, characterized in that: include: Performing a humidification process on the memristor so that the dielectric layer is in a first phase; Heating the memristor to place the dielectric layer in the second phase; Wherein, the memristor comprises: a substrate, an active electrode, an inert electrode, and a dielectric layer arranged between the active electrode and the inert electrode, and the material of the dielectric layer is a phase change material; The dielectric layer is transformed from the first phase to the second phase after being heated, and is transformed from the second phase to the first phase after being humidified; The temperature of the heating treatment is 160°C-200°C; The humidity of the humidity treatment is 80-100%; The phase change material is perovskite, selected from one of CsPbIBr2, CsPbI3, CsPbI2Br, and CsPbBr3.
2. The control method according to claim 1, characterized in that: The deposition thickness of the dielectric layer is 50-80 nanometers.
3. The control method according to claim 1, characterized in that: The material of the substrate is one or more of silicon oxide, glass, quartz, polyethylene naphthalate, and polyethylene terephthalate.
4. The control method according to claim 1, characterized in that: The material of the active electrode is one of silver, copper, nickel, lithium and sodium.
5. The control method according to claim 1, characterized in that: The material of the inert electrode is one of indium tin oxide, aluminum, platinum, gold, titanium, graphene, and fluorine-doped tin oxide.